2022
DOI: 10.1002/vms3.742
|View full text |Cite
|
Sign up to set email alerts
|

Use of native chicken breeds (Gallus gallus domesticus) for the development of suitable methods of Cantabrian capercaillie (Tetrao urogallus cantabricus) semen cryopreservation

Abstract: Background:The Cantabrian capercaillie (Tetrao urogallus cantabricus) is critically endangered. This subspecies has the lowest genetic variability and it is in regression. It belongs to Phasianidae family; therefore, the domestic chicken (Gallus gallus domesticus) could be a good model for developing reproductive technologies for use in capercaillie populations with low availability of animals.Objectives: In this study, we analyzed the response of capercaillie sperm to the freezing-thawing process for contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…The current study showed that the 3% DMA group exhibits significantly (p < 0.05) higher proportions of TMOT and PROG motility compared to the 6% and 9% DMA groups. This result is supported by previous research which reported higher sperm motility at 3% DMA than the other treatments in local Egyptian strains (Dokki-4 and El-salam) [31] and Mediterranean chicken breeds [7], as well as in the Birchen Leonesa breed and wild birds [32]. Abouelezz et al [7] reported that the native Mediterranean chicken sperm is sensitive to DMA, and concentrations lower than 6% are recommended, while O'Brien et al [32] stated that the EK media improved the cryopreservation results with 4% DMA levels compared to the lower levels.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The current study showed that the 3% DMA group exhibits significantly (p < 0.05) higher proportions of TMOT and PROG motility compared to the 6% and 9% DMA groups. This result is supported by previous research which reported higher sperm motility at 3% DMA than the other treatments in local Egyptian strains (Dokki-4 and El-salam) [31] and Mediterranean chicken breeds [7], as well as in the Birchen Leonesa breed and wild birds [32]. Abouelezz et al [7] reported that the native Mediterranean chicken sperm is sensitive to DMA, and concentrations lower than 6% are recommended, while O'Brien et al [32] stated that the EK media improved the cryopreservation results with 4% DMA levels compared to the lower levels.…”
Section: Discussionsupporting
confidence: 88%
“…This result is supported by previous research which reported higher sperm motility at 3% DMA than the other treatments in local Egyptian strains (Dokki-4 and El-salam) [31] and Mediterranean chicken breeds [7], as well as in the Birchen Leonesa breed and wild birds [32]. Abouelezz et al [7] reported that the native Mediterranean chicken sperm is sensitive to DMA, and concentrations lower than 6% are recommended, while O'Brien et al [32] stated that the EK media improved the cryopreservation results with 4% DMA levels compared to the lower levels. On the other hand, DMA addition at the concentration of 6% can retain sperm motility and fertility after cryopreservation in chicken [33], 8% DMA in turkey [34], and red jungle fowl [6].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation